Mechanical Properties and Control Rockburst Mechanism of Coal and Rock Mass with Bursting Liability in Deep Mining - Ming-tao Gao; Zhen-qi Song; Hui-qiang Duan; Heng-qi Xin; Jian-quan Tang (Shock and Vibration)
In order to study the mechanism of the dynamic disaster of rockburst in a deep coal mine and the prevention and control measures of weakening shock, the MTS815.03 servocontrolled rock mechanics test system is used to test the coal, rock, and combined specimens with the buried depth of nearly 1200 m in Xinwen Mining Area. And their mechanical properties, energy evolution, and bursting properties are studied and analyzed. The rationality of the test results is also verified by the in-situ engineering practice. The key conclusions are as follows: (1) There is a relation between the ratio of elastic modulus Ee before peak strength to descending modulus Ed after peak strength and the bursting properties. For the fractured coal, the descending modulus Ed is relatively small, and the Ee/Ed is relatively large and presents progressive ductile failure with low probability and risk of rockburst. For the less fractured rock, the descending modulus Ed is relatively large, and the Ee/Ed is relatively small and presents brittle failure, which is very similar to the characteristics of rockburst. (2) For the same type of rock, with the increase of confining pressure, the Ee/Ed gradually increases, indicating the reduction of rockburst strength. Therefore, the greater the support strength provided to the surrounding rock surface of the roadway, the smaller the failure degree of rockburst. (3) With the increase of confining pressure, after peak strength, the elastic energy of coal specimens decreases slowly, and the dissipated energy increases slowly, indicating that the increase of confining pressure can effectively limit the energy dissipation and release after coal specimen failure. So, in the in-situ engineering practice, it is an important measure to improve the surface restraint and support strength of the coal roadway for reducing the occurrence intensity and probability of rockburst. (4) The combined measures of “the mining of double liberating seam + the implementation of large-diameter pressure relief borehole in advance of working face” is the very effective way to eliminate the rockburst accidents of working face in a protected coal seam and has an important guiding significance for the safe mining of rockburst mine.